Paku Baja : Upaya Meningkatan Karakter Siswa Melalui Sosialisasi Unggah - Ungguh Basa Jawa - Hardono Hardono; Kezia Kurnia; Syarofina Hernila; Catur Wulandari; Shidiq Hema; Endah Tri; Savina Dina; Anastasya Gladly; Gabriella Caroline (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Politeness, for Javanese people is very important. Javanese culture highly upholds politeness or Eastern customs. A person's manners can be seen and assessed from their behavior (patrap) and speech (subasita/unggah-ungguh). So there is a proverb that says "Ajining raga tumata ing busana, ajining dhiri gumantung kedaling lathi", this expression implies that whether someone is good or not can be assessed from the way they dress and speak. Along with the development of the era of globalization today, Javanese cultural values ​​are increasingly being degraded. . The younger generation who are reluctant to apply the manners of Javanese language which are considered complicated, they also have difficulty using polite and respectful language (ragam krama). The reason is that manners are considered difficult so that they (especially young people today) are afraid that if they apply the correct manners incorrectly, they will be considered impolite or arrogant; the second reason is that Javanese language (ungguh-ungguh) is perceived as not bringing progress to their future ideals. Thus, socialization of Javanese politeness was held for elementary school students, with the aim of improving students' character and instilling politeness from an early age. Socialization was carried out for students in grades 5 and 6 at SDN 01 Kayumas and SDN 02 Kayumas. The delivery of simple materials and direct practice made it easier for students to understand the politeness material.